Tuberculosis Among Young People on Rise in Sri-Lanka (An Analysis of Trend and Associated Factors) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2018)
Introduction: A descriptive cross sectional study was carried out in 5 randomly selected districts i.e Gampaha, Kandy, Badulla, Nuwara Eliya and Ratnapura during the period of March to September 2014. The general objective of the study was to describe the trend of TB among young population over past 6 years in Sri Lanka and to determine contributory factors associated with TB among young population.Methodology: The study was carried out in two stages. The first stage was analysis of the trend of TB over the 6 year period of 2008-2014. The analysis of the trend was carried out using the existing secondary data at the Medical Records Division of the National Programme for Tuberculosis Control and Chest Diseases (NPTCCD). Trend was analyzed for new cases of TB patients of 15--34 years of age and separately for 15-24 and 25-34 age groups and for each type of new TB cases. The second stage was a descriptive cross sectional study which was carried out to determine the associated factors. All the patients (new/ retreatment)in age group of 15-34 years and registered at the selected district chest clinics with confi rmed TB were selected as the study subjects. Operational Definitions were used to identify confi rmed TB cases ie, Sputum smear positive TB, smear negative pulmonary TB and Extra pulmonary TB. The data were collected using a pre tested interviewer administered questionnaire by the District Tuberculosis Control Officers attached to the relevant District Chest Clinics.Result: The main findings of the study were, The two peaks of TB incidence were observed in the trend across age groups and first one was in the age group of 25-34 years second peak in the age group of 45-54.Overall trend of TB in the country is more towards the older age groups (over 45 years), but shift to younger age groups were observed in 15 out of 16 districts in the country. A total of 223 patients were included in the descriptive study. The highest proportion (34%) of study population was from the district of Gampaha while least proportion (10%) of it was from Nuwara Eliya. Nearly 53% of the study population was above 25 years of age with the sex ratio of 1:1. A majority (68%) of the study population was Sinhalese while nearly 70% of the study population has passed the O/L, A/L, Diploma or a degree. About one third of the study population was unemployed. Nearly half (50.4%) of the study population was having monthly income of about Rs. 20,000.00 or above. 31% of the study population were current or past alcohol consumers and 29% were smokers and 7% of the study population were current or past cannabis consumers. Majority (77%) of the study population were under-nourished while 14% of them were less than 15 kg/m2. Nearly three fourth (72%) of the study population have been diagnosed by a consultant. Statistically signifi cant associations were found between the age category and more than 3 family members (χ2=5.063, df=1, p